2003
DOI: 10.1074/jbc.m300703200
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenic Protein 4 Produced in Endothelial Cells by Oscillatory Shear Stress Stimulates an Inflammatory Response

Abstract: Atherosclerosis is now viewed as an inflammatory disease occurring preferentially in arterial regions exposed to disturbed flow conditions, including oscillatory shear stress (OS), in branched arteries. In contrast, the arterial regions exposed to laminar shear (LS) are relatively lesion-free. The mechanisms underlying the opposite effects of OS and LS on the inflammatory and atherogenic processes are not clearly understood. Here, through DNA microarrays, protein expression, and functional studies, we identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
309
1
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 270 publications
(335 citation statements)
references
References 38 publications
19
309
1
6
Order By: Relevance
“…Inflammatory processes have been linked to BMP4-up-regulation. 52,53 We thus hypothesize, that stress-induced inflammation may shift the BMP4/noggin balance toward BMP4, thereby increasing the p75NTR expression. Moreover, BMP4 is able to induce SP expression in naive neurons 54,55 thereby contributing to the increase of SP ĎŠ neurons observed in stressed catagen skin.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory processes have been linked to BMP4-up-regulation. 52,53 We thus hypothesize, that stress-induced inflammation may shift the BMP4/noggin balance toward BMP4, thereby increasing the p75NTR expression. Moreover, BMP4 is able to induce SP expression in naive neurons 54,55 thereby contributing to the increase of SP ĎŠ neurons observed in stressed catagen skin.…”
Section: Discussionmentioning
confidence: 99%
“…Confluent endothelial monolayers grown in 100-mm tissue culture dishes were exposed to an arterial level of unidirectional LS (15 dyn/cm 2 ) or OS with directional changes of flow at 1 Hz cycle (ĎŽ5 dyn/cm 2 ) for 1 day by rotating a Teflon cone (0.5°cone angle) as described previously. 19 One hour before shear, the monolayers were washed and changed to 10 mL of fresh shear medium (the growth medium without serum).…”
Section: Mouse Aortic Endothelial Cell Culture and Shear Stress Studiesmentioning
confidence: 99%
“…Mouse aortic endothelial cells (MAEC) obtained from the thoracic aortas of C57/BL6 mice were isolated, cultured in growth medium (Dulbecco modified Eagle's medium [DMEM] containing 20% fetal bovine serum [FBS], 100 g/mL endothelial cell growth supplement [ECGS, Sigma], and 2.5 U/mL heparin) as described, 19 and used between passages 7 to 10. Confluent endothelial monolayers grown in 100-mm tissue culture dishes were exposed to an arterial level of unidirectional LS (15 dyn/cm 2 ) or OS with directional changes of flow at 1 Hz cycle (ĎŽ5 dyn/cm 2 ) for 1 day by rotating a Teflon cone (0.5°cone angle) as described previously.…”
Section: Mouse Aortic Endothelial Cell Culture and Shear Stress Studiesmentioning
confidence: 99%
“…3,5,11 Importantly, recent studies confirmed a striking upregulation of BMP-2/4 in atherosclerotic lesions. [2][3][4] Despite the growing evidence for the physiological/pathophysiological importance of BMP-2 in blood vessels, the mechanisms regulating endothelial BMP-2 expression have not yet been elucidated. Previously, we 12 have demonstrated that in coronary arteries in hyperhomocysteinemia, vascular inflammation and upregulation of TNF-␣ are associated with an increased vascular BMP-2 expression.…”
mentioning
confidence: 99%
“…Key Words: free radicals Ⅲ cytokines Ⅲ growth factors T he transforming growth factor superfamily member cytokine, bone morphogenetic protein-2 (BMP-2), was originally detected in cartilage and bone 1 ; however, recent studies from this and other laboratories demonstrated that vascular endothelial and smooth muscle cells are also a significant source of BMPs. [2][3][4][5][6] First genetic analysis of patients with primary pulmonary hypertension indicated that a vascular BMP-2/BMP receptor system plays an important role in vascular physiology. 7,8 Indeed, BMP-2 has been shown to regulate a host of cellular functions, 2,4,5,9 including cardiovascular development, 9 neovascularization in tumors, 10 and smooth muscle cell chemotaxis in response to vascular injury.…”
mentioning
confidence: 99%